Abnormal maturation of the resting‐state peak alpha frequency in children with autism spectrum disorder. Issue 11 (11th April 2019) - Edgar, J. Christopher; Dipiero, Marissa; McBride, Emma; Green, Heather L.; Berman, Jeffrey; Ku, Matthew; Liu, Song; Blaskey, Lisa; Kuschner, Emily; Airey, Megan; Ross, Judith L.; Bloy, Luke; et al.
Abstract: Age‐related changes in resting‐state (RS) neural rhythms in typically developing children (TDC) but not children with autism spectrum disorder (ASD) suggest that RS measures may be of clinical use in ASD only for certain ages. The study examined this issue via assessing RS peak alpha frequency (PAF), a measure previous studies, have indicated as abnormal in ASD. RS magnetoencephalographic (MEG) data were obtained from 141 TDC (6.13–17.70 years) and 204 ASD (6.07–17.93 years). A source model with 15 regional sources projected the raw MEG surface data into brain source space. PAF was identified in each participant from the source showing the largest amplitude alpha activity (7‐13 Hz). Given sex differences in PAF in TDC (females > males) and relatively few females in both groups, group comparisons were conducted examining only male TDC ( N = 121) and ASD ( N = 183). Regressions showed significant group slope differences, with an age‐related increase in PAF in TDC ( R 2 = 0.32) but not ASD ( R 2 = 0.01). Analyses examining male children below or above 10‐years‐old (median split) indicated group effects only in the younger TDC (8.90 Hz) and ASD (9.84 Hz; Cohen's d = 1.05). In the older ASD, a higher nonverbal IQ was associated with a higher PAF. In the younger TDC, a faster speed of processing was associated with a higher PAF. PAF as a marker for ASD depends on age, with a RS alpha marker of more interest in younger versus older children with ASD. Associations between PAF and cognitive ability were also found to be age and group specific.